Comparison of Erysiphe cichoracearum and E. cruciferarum and a Survey of 360 Arabidopsis thaliana Accessions for Resistance to These Two Powdery Mildew Pathogens - Adam, L.; Ellwood, Simon; Wilson, I.; Saenz, G.; Xiao, S.; Oliver, Richard; Turner, J.; Somerville, S. (1999)
In previous work, UEA1 and UCSC1, two geographically distinct, powdery mildew isolates, were recognized for their ability to infect Arabidopsis thaliana. We have clarified the identity of these isolates by determining their host ranges, reexamining their morphology, and comparing their DNA sequences for the 5.8S ribosomal RNA and two flanking internal transcribed spacer sequences. These experiments confirm that UEA1 is a member of Erysiphe cruciferarum and that UCSC1 belongs to E. cichoracearum. Interactions of the two Erysiphe isolates with 360 A. thaliana accessions were examined to provide a comprehensive profile of naturally occurring powdery mildew resistance in this weedy species. The majority of A. thaliana accessions (213) were susceptible to both isolates. Among the accessions exhibiting some degree of resistance, most (84) responded differentially to UEA1 and UCSC1 and the remainder were resistant to both isolates. Notably, resistance to UCSC1 cosegregated with RPW7, a locus previously demonstrated to confer resistance to UEA1 in Ms-0 × Landsberg (erecta) crosses. With this large collection of resistant accessions, questions about species specificity, genetic diversity and the evolution of resistance to powdery mildews can be addressed.